Ecological role of free-living bacteria in the microbial food web of the temporarily open/closed East Kleinemonde Estuary, South Africa - Allan, Elizabeth Louise (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2008)
The main aim of this study was to assess the "top-down" and "bottom-up" control of bacterial production in the small temporarily open/closed East Kleinemonde Estuary, situated on the south-eastern coastline of southern Africa. Spatial and temporal patterns in bacterial abundance, biomass and production and the importance of abiotic and biotic factors were investigated over the period May 2006 to April 2007. The trophic interactions between bacteria, phytoplankton, nanoflagellates (< 20 Î¼m), microzooplankton (< 200 Î¼m) and mesozooplankton (< 2 000 Î¼m) were investigated during winter and summer. Bacterial abundance, biomass and production ranged between 1.00 Ã— 10â ¹ and 4.93 Ã— 10â ¹ cells 1â »Â¹, 32.4 and 109 Î¼g C 1â »Â¹ and 0.01 and 1.99 Î¼g C 1â »Â¹ hâ »Â¹, respectively. With a few exceptions there were no spatial patterns in the values. Bacterial abundance, biomass and production, however, demonstrated a distinct temporal pattern with the lowest values consistently recorded during the winter months. Nanoflagellate and bacterial abundances were significantly correlated to one another (lower reaches: r = 0.818, p < 0.001; middle reaches: r = 0.628, p < 0.001; upper reaches: r = 0.484, p < 0.05) suggesting a strong predator-prey relationship. The frequency of visibly infected bacterial cells and the mean number of virus particles within each bacterial cell during this study demonstrated no temporal or spatial patterns and ranged from 0.5 to 6.1 % and 12.0 to 37.5 virus particles per bacterium, respectively. Viral infection and lysis was thus a constant source of bacterial mortality throughout the year. The estimated percentage of bacterial production removed by viral lysis ranged between 7.8 and 88.9% of the total which suggests that viral lysis represented a very important source of bacterial mortality during this study. The biological interactions between the selected components of the plankton community demonstrated that among the heterotrophic components of the plankton, the nanoflagellates were identified as the most important consumers of bacteria and small phytoplankton cells (< 20 Î¼m). In the presence of microzooplankton the impact of the nanoflagellates on both the bacteria and phytoplankton was reduced, indicating that larger heterotrophs were preying upon the nanoflagellates. Mesozooplankton, however, appeared to exert the greatest impact on nanoflagellates. In the cascading experiments, the data suggest that mesozooplankton consume nanoflagellates, which resulted in a decrease in the predation impact of these organisms on the bacteria. This result is consistent with predator-prey cascades. The presence of the larger heterotrophs therefore, mediates the interactions between the primary bacterivores, the nanoflagellates, and the bacteria within the temporarily open/closed East Kleinemonde Estuary.
Keywords: Bacterial growth -- South Africa -- Eastern Cape; Estuarine ecology -- South Africa -- Eastern Cape; Estuaries -- South Africa -- Eastern Cape; Microbial ecology -- South Africa -- Eastern Cape; Nutrient cycles -- South Africa -- Eastern Cape; Food chains (Ecology)